Prevalence of undernutrition and anemia in 6–24-month-old children in rural South India: Assessing the target population for a multiple biofortified crops feeding trial - Jones, Camille; Gannon, Bryan; Hackl, Laura; Finkelstein, Julia L.; Wesley, Bonam; Haas, Jere D.; Mehta, Saurabh (American Society for Nutrition, 2020)
To characterize anemia and anthropometry in children in rural South India: 1. Report the prevalence of undernutrition and anemia; 2. Examine associations with demographic, socio-economic, and clinical characteristics among 6–24-month-old children screened for participation in a randomized controlled feeding trial.